Successfully managing ADHD : a handbook for SENCOs and teachers - O'Regan, Fintan J. (Fintan Joseph), 1960- (Milton Park, Abingdon, Oxon : Routledge, 2014)
'Behaviour issues in general, and ADHD in particular, is always a high priority in schools. Teachers are constantly searching for practical guidance on how to manage learners who find it difficult to concentrate and stay on task for any length of time, sometimes presenting challenging behaviour in the classroom and disrupting learning for other students. Fintan O'Regan provides a user-friendly resource for busy teachers, showing them how to offer practical and effective strategies and models of good practice to practitioners, and signposting further sources of information. Chapters in this essential book cover topics such as: How can we manage ADHD behaviour? How can we help non-traditional learners access the curriculum? Working with parents of children with ADHD Making transitions less problematic Exporing other options for managing ADHD The role of medication and how/when it can help Written by one of the UK's leading experts on the topic, SENCOs, teachers, behaviour management staff and senior leaders will find invaluable, practical and up-to-date information and advice on ADHD and will be able use the additional resources provided as a continuing professional development tool with colleagues in all phases'--
Includes bibliographical references and index.
Keywords: Attention-deficit-disordered children -- Education -- Great Britain -- Handbooks, manuals, etc; Special education -- Great Britain -- Handbooks, manuals, etc